EKSISTENSI KOMUNITAS LESBIAN GAY BISEKSUAL TRANSGENDER (LGBT) DI KABUPATEN BONE - Musliamin Musliamin (Institut Agama Islam Negeri Bone, 2021)
This journal study about the existence of lesbian, gay, bisexual and transgender (LGBT) at the town sub district in Bone regency with the research focus is: how is the lesbian of gay transgender community in Bone regency observed from sociological and juridical studies. The aims of this reserach are to analyze events in the field as the fact is that. While the method used in this research was descriptive qualitative. This method aims to obtain a good depiction, obvious and can give data accurately about the object that will be researched. This research showed that the existence of lesbian of gay bisexual transgender (LGBT) at the town sub district in Bone regency was real of its existence. In the sociological study stated the society assumed that the existence of this community disturb their activity, because of some things that they did is not like what have been done by society commonly. However, in the juridical study in Islam perspective, its existence impinge, because of opposing with Islam education such as what have been done by former community in this case clan of Luth Prophet. While, in the law of positive also contradictive because of representing deed action to impinge morality in the formula rule of crime which is arranged in section of statute 292 KUHP.